Penanggulangan Tindak Pidana Illegal Fishing Di Indonesia - Amin, Muhammad Nur; Deshaini, Liza; Sudarna, Sudarna (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2023)
Overcoming the criminal act of illegal fishing in Indonesia is: Vessel monitoring System (VMS), monitoring efforts in Indonesian waters, Law enforcement efforts and the factors that become obstacles in overcoming the crime of illegal fishing in Indonesia, obstacles in general are legal substance, legal apparatus, facilities and means. citizen's awareness. And the obstacles in the legal process are legal apparatus, facilities and means, public awareness, obstacles in the legal process, investigation stage, investigation stage and prosecution stage.